International signs to provide guidance to persons at airports. - International Civil Aviation Organization (Montreal, Quebec : International Civil Aviation Organization, 1984)
"After more than ten years of use and experience the signs have been reviewed by ICAO and ... certain modifications, deletions and additions have been made"--Foreword.
On cover: Approved by the Council and published by its decision.
"Doc 9430-C/1080."
Keywords: Signs and signboards